Pengaruh Coaching, Mentoring dan Keterlibatan Kerja terhadap Keberlanjutan Organisasi melalui Produktivitas Karyawan dalam Lingkungan Kerja yang Dinamis - Lily Yuntina; Tubagus Hedi Saepudin; Erni Pratiwi Perwitasari; Agus Setiawan; Agus Suhendra (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to develop hypotheses regarding the factors influencing sustainable organizations with the mediating role of employee productivity, particularly in the airline sector. The method applied is a literature review with a descriptive qualitative approach. Data were collected through the review of various relevant academic articles and books, sourced from reputable databases such as Thomson Reuters, Springer, Taylor & Francis, Scopus Q2–Q4, Emerald, Elsevier, Sage, Web of Science, Sinta 2–5 Journals, DOAJ, EBSCO, Google Scholar, Copernicus, and other digital references. The analysis technique used is comparative analysis of previous research findings to identify similarities and differences. The findings indicate significant relationships between organizational factors, employee productivity, and sustainability. First, coaching, mentoring, and work engagement positively influence employee productivity. Second, these factors also have a direct impact on the establishment of sustainable organizations. Third, employee productivity serves as a crucial mediating variable linking coaching, mentoring, and work engagement to organizational sustainability. Thus, this study emphasizes that strengthening coaching and mentoring practices, along with enhancing work engagement, not only improves employee productivity but also contributes to long-term organizational sustainability. The implication is that airline companies should prioritize human resource development strategies as a key driver to achieve sustainable goals and maintain competitiveness in a dynamic industry.